Does Incentives Schemes and Working Relationship Affect Auditor Whistleblowing Intention? - Mapuasari, Supeni Anggraeni; Rusliadi, Gading Anindita; Fitriana, Vita Elisa (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2023)
Whistleblowing is one of the key oversight mechanisms in response to many corporate financial scandals. This mechanism aids in the upkeep of qualified audit methods and judgment in the public accounting firm. Workplace relationships and incentive programs may have an impact on auditors' intentions to report misconduct. This research is one of the few that tests experimentally whether workplace relationship and incentive programs can increase the influence of the desire to disclose fraudulent financial reporting. This study makes use of 60 final-year students who have worked as interns at public accounting firms, utilizing the true experimental-post-test control design method. The data was analysed with ANOVA test by utilizing 2x2 experimental design. The presence of incentive awards was found to positively correlate with auditors' propensity to report misconduct. The relationship between incentives to whistleblowing intention getting stronger when the working relationship between the whistle-blower to the reported senior is close. The findings contain important implications to enrich literature and practical contribution towards whistleblowing discussion. Whistleblowing adalah salah satu mekanisme pengawasan utama dalam menanggapi banyak skandal keuangan perusahaan. Mekanisme ini membantu dalam pemeliharaan metode audit yang berkualitas dan penilaian di kantor akuntan publik. Hubungan di tempat kerja dan program insentif dapat berdampak pada niat auditor untuk melaporkan pelanggaran. Penelitian ini adalah salah satu dari sedikit yang menguji secara eksperimental apakah hubungan di tempat kerja dan program insentif dapat meningkatkan pengaruh keinginan untuk mengungkapkan kecurangan pelaporan keuangan. Responden dalam penelitian ini adalah mahasiswa tahun terakhir yang pernah menjalankan magang di kantor akuntan publik. Dengan mempergunakan metode eksperimen tulen post-test, penelitian ini mengujikan pengaruh antar variabel dengan alat statistic ANOVA berdesain 2x2. Keberadaan program insentif secara empiris berpengaruh positif dalam meningkatkan intensi whistle blowing. Hubungan ini semakin kuat saat pelapor dan terlapor memiliki kedekatan hubungan kerja. Temuan riset ini menarik dan dapat memperkaya kajian literatur dan praktik terkait whistle blowing di dunia audit.